2014
DOI: 10.1111/jspn.12098
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a school‐based academic asthma health education and counseling program on fostering acceptance of asthma in older school‐age students with asthma

Abstract: Purpose The purpose was to evaluate the effectiveness of the academic asthma education and counseling SHARP program on fostering psychosocial acceptance of asthma. Design and Methods This was a phase III, two-group, cluster randomized, single-blinded, longitudinal study. Students from grades 4 and 5 (N = 205) with asthma and their caregivers completed surveys at pre-intervention and at 1, 12, and 24 months post-intervention. Analysis involved multilevel modeling. Results All students demonstrated significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Certified elementary school teachers are educated to instruct students in diverse subject matter using a variety of techniques and methods. Teachers were trained and supervised by nurse specialists in pediatric asthma and psychiatric/mental health counseling (Kintner, Cook, Marti, Allen et al, ; Kintner, Cook, Marti, Gomes et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certified elementary school teachers are educated to instruct students in diverse subject matter using a variety of techniques and methods. Teachers were trained and supervised by nurse specialists in pediatric asthma and psychiatric/mental health counseling (Kintner, Cook, Marti, Allen et al, ; Kintner, Cook, Marti, Gomes et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Its effectiveness for psychosocial, behavioral, and quality of life outcomes compared to a well-established non-academic asthma education program, Open Airways for Schools (OAS; Clark et al, 2004; Evans et al, 1987), has been reported elsewhere (Kintner, Cook, Marti, Allen et al, 2015; Kintner, Cook, Marti, Gomes et al, 2015). …”
Section: Evaluation Of Sharp To Datementioning
confidence: 99%
See 1 more Smart Citation
“…We developed two instruments based on extensive reviews of asthma literature: Knowledge of Asthma Survey 46,47 and General Health History Survey 46–48 . We extracted statements and themes from our qualitative interviews to create three instruments: Acceptance of Asthma Questionnaire, 46,48,49 Beliefs about Asthma Questionnaire, and Participation in Life Activities Scale 3,4 . Findings of a series of instrumentation studies guided revisions to improve the psychometric properties of the acceptance and beliefs questionnaires over time.…”
Section: Theory Evaluation and Augmentationmentioning
confidence: 99%
“…Of the studies focused on children, most address interventions for school-aged children [13][14][15][16][17][18][19][20][21][22]. The literature is lacking in studies addressing the creation of education material for children, especially those that include information about self-regulating behaviors.…”
Section: Audience: Childrenmentioning
confidence: 99%